Semi-Nonparametric Estimation of Energy Demand in Tunisia - Landolsi, Monia; Miled, Kamel Bel Hadj (International Journal of Energy Economics and Policy, 2024)
In this paper, we have studied the possibilities of substitution between different forms of energy at the sectoral level in Tunisia. Indeed, we estimated a globally flexible functional form of Fourier type using the iterative Zellner’s seemingly unrelated regression (ITSUR). Contrary to several previous studies in the literature, we calculated the price (proper and crossed) and income elasticities, the elasticities of substitution in the sense of Allen, as well as the elasticities of substitution in the sense of Morishima for the period (1980-2017). The results show that price and income elasticities differ from one energy product to another and from one sector to another, depending on the destination (final or intermediate) and the nature of use. Additionally, the findings suggest that energy demand is more sensitive to changes in income rather than changes in price. It is noteworthy that the absolute value of price elasticity is lower than that of income elasticity. Implementing an appropriate pricing policy can help limit the income effect and encourage economic agents to make efforts to save energy. Our results also indicate that any pricing policy aiming to reduce energy consumption must consider the possibilities of substituting between products. Otherwise, this policy may yield results contrary to the intended objectives.